The role of discourses in understanding institutional stability and change – an analysis of Dutch flood risk governance. Issue 1 (2nd January 2022) - Kaufmann, Maria; Wiering, Mark
ABSTRACT: Societies are faced with aggravating environmental challenge. To respond to these challenges with desired institutional changes, we need to understand the processes of institutional stability and change. This paper adds to the literature on institutional dynamics by focusing particularly on the various roles of discourses. It examines the interaction of emerging discourses and pre-existing governance arrangements and their outcomes; not by zooming in on a specific policy concept but by scrutinising the long-term development of a policy domain, namely flood risk governance (FRG) in the Netherlands. Based on an abductive analysis, we created a typology that shows the influence of emerging discourses on stability or change of pre-existing governance arrangements. At the one end of the ideal-typical continuum, the pre-existing arrangement remains relatively unchanged or is even strengthened. At the other end of the continuum, little remains of the pre-existing arrangement, i.e. emerging discourses are institutionalised, substituting existing institutions with new rules or organisations. Between these two extremes, several hybrid types can be identified (e.g. absorbing, merging, layering, weakening). Although there is clear evidence of incremental changes and adjustments in the Dutch FRG, fundamental changes are missing due to the path dependency of the strong hydro-engineering governance arrangement.